A comparative study on anaerobic capacity, fatigue index, and lactate after effort between female volleyball players and students of the College of Physical Education (Journal of the College of Basic Education, 2022)
Study Objective: To identify the effect of anaerobic effort on anaerobic capacity and its level of decline in terms of fatigue index for six repetitions of quick sprints in a sample of club players in volleyball and volleyball practices, and the effect of anaerobic effort on the concentration of lactate in the blood after six repetitions of quick sprints in a sample of club players and volleyball practices volleyball and to identify the differences in the concentration of lactate in the blood between the two samples. The researcher used the RAST test as a measure of the anaerobic ability to run for a distance of 35 meters. It is repeated six times and 10 seconds are allocated for recovery between one repetition and another. After completing the effort in the seventh minute, blood was drawn to measure the level of lactate in the blood. The outcome of the study